Chemical Petrology of Tertiary Flood Basalts from the Scoresby Sund Area. : With Electron Probe Analyses by E. L. Gasparrini. - Fawcett, J. J.; Brooks, C. K.; Rucklidge, J. C.; Gasparrini, E. L. (Meddelelser om Grønland, 1973)
Sequences of basalts have been sampled in a number of profiles in the upper part of the basalt plateau of Kong Christian IX’s Land. The flows are faulted and tilted near the coast but apparently undisturbed inland. Nowhere in the investigated area were intrusives found, but sediments and pyroclastic horizons (including a palagonitic brecceia) were observed in a few localities. The bulk of the flows are subacrial. These basalts are seen under the microscope to be typical tholeiites, being made up of plagioclase (labradorite), clinopyroxene and opaque oxides. Olivine may be present occasionally and pigeonite sporadically. The glassy breccia contains two types of glass (fresh and hydrated) with olivine and plagioclase microphenocrysts. Chemically the lavas form an extremely homogeneous group and have with one exception quartz and hypersthene in the norm. The fact that this one exception is the most reduced of the analyses suggests that the appearance of normative quartz may be secondary and that the magmas originally were olivine-hypersthene normative. Specific chemical characteristics of these lavas include high iron and TiO 2 contents, and low K2O. They differ from the Skaergaard magma in that they are not high-alumina types and they do not have such a high magnesium content. Comparisons have been drawn with ocean-floor tholeii tes and tholeiites from other regions of the North Atlantic province, and although systematic geographic differences may exist in this province they are minor, with better data than available at present being required to confirm them. A large number of mineral analyses, especially of pyroxenes, has been carried out by electron microprobe. The pyroxenes show extensive variation both of a normal fractional crystallization type and various "quench" trends towards sub-calcic augites although certain observations do not favour the interpretation of these trends as being due to metastable crystallization. The feldspars show relatively restricted variation in spite of the complex zoning shown by many of the phenocrysts. Coexisting oxide phases give, in general, values of P02 and temperature similar to that found by other workers although some samples have suffered reequilibration and are anomalous. Interstitial glass has undergone hydration and does not appear to have the composition of a late differentiate.